Effect Of Condom Utilization On Sexuall Transmitted Infection Among Female Sex Workers, In Tulungagung District, East Java, Indonesia - Hanifah, Ainun; Probandari, Ari Natalia; Pamungkasari, Eti Poncorini (UI Scholars Hub, 2019)
One effective strategy for preventing sexually transmitted infection (STI) incidence and providing protection for female sex workers (FSWs) from their sexual partners is correct and consistent condom use behavior. This study examined the effect of condom use on STI among FSWs in Tulungagung District, East Java. This analytic and observational study using a cohort prospective design was conducted at Ngujang ex- prostitution area and Gunung Bolo prostitution area, Tulungagung District, from November to January 2017. The total sample selected was 90 FSWs. Data was collected through a set of questionnaires and tracking condom use in a diary. Data were analyzed by using Pearson’s chi-square, t-test and logistic regression models at a significance of 0.05. Bivariate analysis with chi-square test showed that STI was affected by period of condom use, ratio of number of condom used to number of times the FSW had sex, condom use, age, number of customers, skill in using condoms, tarifts for sexual services, and length of working as an FSW. Results of multivariate logistic regression showed an influence in ratio of condom use to having sex, number of condoms, and number of customers. In conclusion, the incidence of STI is influenced by the ratio of condom use to having sex, number of condoms used, and number of customers in Tulungagung District.